2021
DOI: 10.1093/mnras/stab782
|View full text |Cite
|
Sign up to set email alerts
|

Appearance versus disappearance of broad absorption line troughs in quasars

Abstract: We present a new set of 84 Broad absorption line (BAL) quasars ( 1.7 < zem< 4.4) exhibiting an appearance of C iv BAL troughs over 0.3−4.8 rest-frame years by comparing the Sloan Digital Sky Survey Data Release (SDSSDR)-7, SDSSDR-12, and SDSSDR-14 quasar catalogs. We contrast the nature of BAL variability in this appearing BAL quasar sample with a disappearing BAL quasar sample studied in literature by comparing the quasar’s intrinsic, BAL trough, and continuum parameters between the two samples.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The changes in the line of sight gas distribution is also suggested in the case of BAL-B and BAL-C through the presence of rapidly varying narrow absorption components as discussed above. Mishra et al (2021) have found the newly appeared BALs are associated with dimming of the quasars. Interestingly, the emergence of BAL-C happens close to the dimming episode in the lightcurve of J1322 + 0524 (see Fig.…”
Section: Photometric Variability Of J1322 + 0524mentioning
confidence: 93%
See 1 more Smart Citation
“…The changes in the line of sight gas distribution is also suggested in the case of BAL-B and BAL-C through the presence of rapidly varying narrow absorption components as discussed above. Mishra et al (2021) have found the newly appeared BALs are associated with dimming of the quasars. Interestingly, the emergence of BAL-C happens close to the dimming episode in the lightcurve of J1322 + 0524 (see Fig.…”
Section: Photometric Variability Of J1322 + 0524mentioning
confidence: 93%
“…13). Mishra et al (2021) interpreted the appearence of a new BAL component as the consequence of lower ionization. Alternatively, it is possible that both the dimming and BAL emergence can be related to changes in the accretion disk structure (see Vivek et al 2012, for discussions in the case of J1333+0012).…”
Section: Photometric Variability Of J1322 + 0524mentioning
confidence: 99%
“…The wind and jet connection from Mehdipour & Costantini (2019) cannot be due to synchronous effects, although the overall history of the AGN could be the connection. Studies of disappearing and appearing BALQSOs (De Cicco et al 2017;Mishra et al 2021) have placed the variational time scale for BALQSO winds, on the order of hundreds of years, to be much shorter than that of radio jets, on the order of Myrs. Therefore the BI to detection fraction correlation lacks the synchronicity one might expect in the evolutionary theory.…”
Section: Radio Interpretationmentioning
confidence: 99%
“…The presence of high-velocity outflows from AGN can be established from the evidence provided by the blue-shifted broad absorption lines (BALs) seen in the spectra of 10-20% of quasi-stellar objects (QSOs) 1 (Weymann et al 1991). BALQSOs are classified into three sub-classes based on the ionization state of the absorbing gas:(a) high-ionization BALQSOs (Hi-BALs) consists of absorption from high-ionization lines such as C , Si , and N (Gibson et al 2008;Filiz Ak et al 2013;Vivek et al 2016;Vivek 2019;Mishra et al 2021) (b) low-ionization BALQSOs (LoBALs) show absorption from low-ionization lines such as Mg and Al along with the high-ionization lines (Voit et al 1993;Vivek et al 2014Vivek et al , 2018Yi et al 2019), and (c) iron-LoBALs (FeLoBALs) are LoBALs with excited fine-structure Fe and/or Fe absorption lines (Vivek et al 2012;McGraw et al 2015). The observed BALQSO fraction is explained either by an orientation model, where the line of sight intersects with the BAL absorbing clouds in 10-20% QSOs (Weymann et al 1991;Elvis 2000), or an evolutionary model, where the QSO spends 10-20% of its lifetime in the BALQSO phase (Farrah et al 2007;Lipari et al 2009).…”
Section: Introductionmentioning
confidence: 99%